Ethical Leadership and Knowledge Hiding behavior: Mechanism Moral Identity - Elmi Yadi; Adi Rahmat; Muhammad Rasyid Abdillah (Jurnal Manajemen, 2022)
Referring to the theory of social exchange, this study examined the direct and indirect relationship between ethical leadership and knowledge hiding behavior through the mechanisms of moral identity. This study uses a quantitative method using 64 respondents permanent lecturers in education institution of Persada Bunda. The results show that ethical leadership is negatively associated with knowledge hiding behavior either directly or through the mechanisms of moral identity. It also shows that ethical leadership has a positive relationship with moral identity, while moral identity has a negative relationship with knowledge hiding behavior. The findings also outline the moral identity mediate the influence of ethical leadership on knowledge hiding behavior. It also explained that ethical leaders with high personality, honesty, morality. and high reliability and understand their impact on employees, can be role models in behavior and form employee moral self-construction such as moral identity.